Redesain Kemasan Makanan Ringan Olahan pada UMKM Center Jawa Tengah dengan Metode Kansei Engineering - Susatyo Nugroho; W, Darminto Pujotom; M. Mujiya Ulkhaq; Dedy Teguh Permadi (Performa: Media Ilmiah Teknik Industri, 2017)
UMKM (Micro, Small, and Medium Enterprises) Center in Central Java Province has 69 types of potential culinary products in the form of snacks. An initial study showed that from 47 MSMEs, there are 45 products which are packaged simply. The research was conducted to create a new packaging design which is appropriate for consumers' needs using Kansei Engineering. The method translates consumers' psychological feelings into new packaging design parameters as well as statistics analysis to elicit design elements in accordance with Kansei Word. Affective and psychological aspects that affect consumers on product packaging are "adorable" and "simplicity". Each component has different Kansei word variables. Adorable component has informative, modern, colorful, interesting, and distinctive variables; whereas Kansei word with the largest weight is colored with the value of 0.961 and the smallest weight is modern with the value of 0.819. Simplicity component has simple, easy-to-carry, and easy-to-open; whereas Kansei word with the largest weight is easy-to-open with the value of 0.927 and the smallest weight is simple with the value of -0.414.